2000
DOI: 10.1016/s0005-2736(99)00240-0
|View full text |Cite
|
Sign up to set email alerts
|

Cold shock in Bacillus subtilis: different effects of benzyl alcohol and ethanol on the membrane organisation and cell adaptation

Abstract: A temperature shift-down of Bacillus subtilis from 40 to 20 degrees C induces an 80 min growth lag. Benzyl alcohol reduced this period to 51 min, whereas ethanol prolonged it up to 102 min. The effect of the two alcohols on the membrane state was investigated by measuring the steady-state fluorescence anisotropy and analysing the lifetime distribution of diphenylhexatriene (DPH) and its polar derivative, TMA-DPH. As followed from the fluorescence anisotropy, the two alcohols exerted similar (fluidizing) effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
27
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
7
27
1
Order By: Relevance
“…Laurdan is an environmentally sensitive probe, and the associated spectral shift reflected a change in membrane polarity (27). For BzA, its addition has been reported to cause a disordered membrane structure (35,43). Our data indicated that a nonlethal concentration of BzA also caused disorder of membrane structures, suggesting that the structural change could increase the permeability of BAC to accelerate BAC accumulation in cells.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Laurdan is an environmentally sensitive probe, and the associated spectral shift reflected a change in membrane polarity (27). For BzA, its addition has been reported to cause a disordered membrane structure (35,43). Our data indicated that a nonlethal concentration of BzA also caused disorder of membrane structures, suggesting that the structural change could increase the permeability of BAC to accelerate BAC accumulation in cells.…”
Section: Discussionmentioning
confidence: 63%
“…They induced interdigitation in the 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) membrane (39,40), causing an increase in proton permeability (41,42). In a Bacillus subtilis strain, the lethal concentration of BzA increased the membrane fluidity (43). For protein structures, BzA induced the aggregation of proteins, such as human interleukin (44) and interleukin-1 receptor antagonist (45), by partially unfolding these proteins (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…However, 29 induced genes showed a significant overlap (P Ͻ 0.01 [two-sided Fisher exact test]) compared to those repressed by cold stress when cells suffer a temperature downshift from 37 to 18°C. Since the B. subtilis cold shock response leads to a growth lag as a consequence of the inhibition of RNA, DNA, and protein synthesis (65), it could be expected that bacterial genes induced by 29, which requires the host machinery to promote its multiplication, were repressed under such conditions. On the other hand, there is an interesting correlation (P Ͻ 0.005 [two-sided Fisher exact test]) between downregulated genes after 29 infection and genes induced when glycerol or gluconate are the carbon sources used by the bacteria, suggesting a phage repression of the metabolism of a broad range of alternative carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…First, we observed a disappearance of anteiso-C 15:0 in favor of iso-C 15:0 for the three strains. The growth-dependent changes in the ratio of terminally branched iso and anteiso fatty acids were suggested in Bacillus subtilis as mechanisms to adjust fluidity (25,31,34) without a change in the saturation level of membrane fatty acids. Second, an accumulation of palmitoleic acid in the wild-type and mutant strains cultivated in the presence of ethanol was obtained (17% [molar percentage] versus 2.5% with acid-grown cells).…”
Section: Discussionmentioning
confidence: 99%